Nanofibrous Spongy Microspheres to Distinctly Release miRNA and Growth Factors to Enrich Regulatory T Cells and Rescue Periodontal Bone Loss - Liu, Zhongning (ACS Nano, 2018)
In addition to T cells’ roles in immune response and autoimmune diseases, certain types of T cells, called regulatory T cells (Tregs), play important roles in microenvironment modulation for resolution and tissue regeneration. However, there are currently few options available other than introducing more Tregs or immunosuppressive drugs to locally enrich Tregs. Herein, poly(L-lactic acid) (PLLA) nanofibrous spongy microspheres (NF-SMS), PLLA/polyethylene glycol (PEG) co-functionalized mesoporous silica nanoparticles (MSN), and poly(lactic acid-co-glycolic acid) microspheres (PLGA MS) are integrated into one multi-biologic delivery vehicle for in situ Treg manipulation, where the MSNs and PLGA MS were utilized to distinctly release IL-2/TGF-β and miR-10a to locally recruit T cells and stimulate their differentiation into Tregs, while PLLA NF-SMS serve as an injectable scaffold for the adhesion and proliferation of these Tregs. In a mouse model of periodontitis, the injectable and biomoleculedelivering PLLA NF-SMS lead to Treg enrichment, expansion and Treg-mediated immune therapy against bone loss. This system can potentially be utilized in a wide variety of other immune and regenerative therapies.